A COMPARATIVE EVALUATION OF PARACETAMOL, IBUPROFEN, AND COMBINATION THERAPY IN THE MANAGEMENT OF ACUTE MUSCULOSKELETAL PAIN: A PROSPECTIVE, OBSERVATIONAL STUDY - KUMARI, PRIYANKA; KUMAR, SANTOSH; SINGH, ASHA (International Journal of Current Pharmaceutical Research, 2026)
Objective: Acute musculoskeletal pain (AMP) is a common clinical condition that significantly impairs functional ability and quality of life. Paracetamol and ibuprofen are widely used analgesics, while combination therapy is believed to offer enhanced pain relief. This study aimed to compare the efficacy and safety of paracetamol, ibuprofen, and their combination in the management of acute musculoskeletal pain. To evaluate and compare analgesic efficacy and tolerability among paracetamol, ibuprofen, and combination therapy using the Numeric Rating Scale (NRS). Methods: A prospective, objective, comparative study was conducted on 90 adult patients with acute musculoskeletal pain. Patients were randomly allocated into three groups (n=30 each): Group A (Paracetamol 1000 mg), Group B (Ibuprofen 400 mg), and Group C (Paracetamol 1000 mg+Ibuprofen 400 mg). Pain intensity was assessed using the NRS at baseline, 2 h, 4 h, and 6 h after administration. Adverse effects were recorded. Data were analyzed using ANOVA and chi-square tests. Results: mean pain reduction at 6 h was highest in the combination group (5.8±1.2) compared to ibuprofen (4.6±1.5) and paracetamol (3.9±1.4), p<0.01. The onset of analgesia was faster with the combination therapy (within 1 hour). Adverse effects were mildand comparable across groups. Conclusion: Combination therapy of paracetamol and ibuprofen provided superior pain relief with a faster onset and acceptable safety profile. It may be recommended for short-term management of acute musculoskeletal pain.